ANALISIS KEPUASAN KONSUMEN TERHADAP PRODUK UNGGULAN SEKTOR MAKANAN KOTA MATARAM (STUDI PADA PRODUK TAHU ABIAN TUBUH) - M. Ilhamudin; Santi Nururly; Rusminah Rusminah (Master of Management, Mataram University, 2020)
This research is aimed at determining the customers satisfaction towards a superior product of Mataram city, Tahu Abian Tubuh. The reseach is descriptive one which using sample survey method. In order to answer the problem proposed, the analytical tools are IKK model and Cartesius diagram. The first model is to measure a difference between what is desired and what is perceived by customers. The second model is to determine which are the attributes have priority to upgrade. The result of this study shows that customers are satisfied to the attributes of tahu Abian Tubuh. However, the flavor needs to have attention, due to the flavor of Tahu is fastly changed. Kata Kunci: Konsumen, kepuasan, Tahu Abian Tubuh